PERSEPSI KONSUMEN TERHADAP SIRUP AIR KELAPA - Andi Windi Indarawati; Azhar Bafadal; Sitti Aida Adha Taridala (Jurnal Sosio Agribisnis, 2016)
Product syrup varies make consumers have different perceptions in choosing syrup products as they wish. Product attributes include marketing stimuli that can affect consumer perception. The purpose of this study was to determine the composition of coconut water taste syrup according to consumer perceptions. The design of this study is the experimental method and descriptive with the stage of product testing laboratory scale and descriptive analysis. A test to determine the composition of flavors preference by consumers conducted by 25 panelists with two replications. Parameters measured were the taste, color, aroma and texture. The results show that the composition according to the taste of the consumer perception is coconut flavors syrup cocopandan water and adding sugar to 65% with an average value of 3.56. The average value of each attribute is a sense of 3.54, 3.72 color, aroma 3,58 and texture 3.56.Keywords: taste, coconut water syrup, Perception.